How Can Temperature Logs Help Identify Permeable Fractures and Define a Conceptual Model of Fluid Circulation? An Example from Deep Geothermal Wells in the Upper Rhine Graben - Jeanne Vidal; Régis Hehn; Carole Glaas; Albert Genter (Geofluids)
Identifying fluid circulation in fracture zones (FZs) is a key challenge in the extraction of deep geothermal heat from natural reservoirs in the Upper Rhine Graben. This study focuses on permeable FZs present within the granitic basement penetrated by deep geothermal well GPK-1 at Soultz and GRT-1 and GRT-2 at Rittershoffen (France). The various temperature (T) log datasets acquired from these wells during production and at equilibrium, with the associated flow logs, allow for the unique opportunity to interpret fluid circulation at the borehole scale. All permeable FZs identified by permeability indicators measured during drilling operations and from image logs spatially coincide with positive or negative T anomalies observed in the T logs during production and/or at equilibrium. However, within the FZs, partially open fractures act as narrower paths for circulation at different temperatures. These temperatures can even be estimated with confidence if the associated flow log is available. The polarity of the T anomalies correlates with the state of equilibrium of the well and thus can change over the well history. During production, the temperature of the water inflow through the fractures can be estimated relative to the mixture of water circulating below the fractures. At thermal equilibrium, the water temperature is estimated with respect to the temperature of the surrounding rock formation. Because temperature fluxes and geothermal fluids are intimately linked, T logs are a useful, reliable, and very sensitive tool to localize the inflow of geothermal water through FZs.